Visual Outcome of Traumatic Cataract at Holy Family Hospital, Rawalpindi - Ali Raza, Tariq Shakoor, Muhammad Imran Janjua (Pakistan Journal of Ophthalmology, 2016)
Purpose: To evaluate the visual outcome of patients with secondary extraction of traumatic cataract with IOL implantation. Study design: Prospective case series. Place and Duration of Study: Department of Ophthalmology, Holy Family Hospital, Rawalpindi from January 2014 to July 2015. Materials and Methods: 38 eyes of 38 patients with traumatic cataract were managed with Cataract Extraction with IOL implantation. The patients were followed up for six months post operatively and final best corrected visual acuity was determined. Results: 38 eyes of 38 patients were studied and there was a male predilection of 3.2:1. The most common age group affected was between 4 and 20 years (50%). Blunt trauma was the cause in 11 (28.9%) patients and penetrating trauma in 27 (71.1%). More than 88% of patients had pre-op BCVA of 6/60 or less. Residual corneal scar due to trauma was present in 24 (63.2%) patients. The final BCVA at 6 months post-op was 6/6 – 6/9 in 11 (28.9%), 6/12 – 6/18 in 21 (55.3%) and 6/24 – 6/36 in 6 (15.8%) patients. Conclusion: Traumatic cataract is a major cause of ocular morbidity in younger age groups and males are commonly affected. If properly managed, good final visual outcome can be achieved in such patients. Key Words: Traumatic cataract, visual acuity, Intraocular lens implantation.